Squamous-cell Carcinoma Arises in Red Parts of Multicolored Tattoo within Months - Paprottka, Felix Julian (Wolters Kluwer Health, 2014)
SUMMARY: Skin cancer formation is on the rise. Only a few case reports, which focus on skin cancer being caused by tattoos, have been published so far. Our aim is to determine whether skin cancer occurrence can be triggered by tattoos. In our presented case, a squamous-cell carcinoma developed inside of the red areas of a multicolored tattoo within months. Furthermore, surgical removal of the cancerously mutated skin area without mutilating the design of the tattoo was challenging. Due to widespread skin alterations in other red areas of the tattoo, those affected skin regions were surgically removed and split-skin grafting was performed. After 1-year follow-up period, the patient has been tumor free. Squamous-cell carcinoma is an unusual reaction that can occur in tattoos. Nevertheless, this skin cancer should be included in the list of cutaneous complications related to tattooing.